Recent advances in the removal of Sunset Yellow dye from wastewater: A review - Cigeroglu, Zeynep; El Messaoudi, Noureddine; Miyah, Youssef; Georgin, Jordana; Franco, Dison S. P.; Benjelloun, Mohammed; Senol, Zeynep Mine (Elsevier, 2024)
The present review focuses on the very latest development with respect to Sunset Yellow FCF (SY) removal from wastewater and dwells mostly on some of the most novel and efficient methods developed in response to everincreasing environmental and health concerns related to this widely used synthetic dye. In this work, adsorption techniques are criticized, considering that the high adsorption capacity of SY offers various environmental benefits. It lowers the concentration of wastewater, which means that fewer dyes are used in effluent processes. These advantages not only contribute to cleaner water bodies but also promote sustainable practices in the textile industry. This review considers in some detail the degradation of SY dye in advanced oxidation processes such as photocatalytic degradation, Fenton-like reactions, and ozonation with regard to general efficiency and cost pertinence. This review, along with biological treatments using isolated strains of bacteria and fungi capable of enzymatically degrading SY dye, offers an eco-friendly alternative against various available chemical methods. Hybrid systems in separation processes are often used for approaches consisting of multiple treatment processes, including biological, physical, and chemical, to completely treat water. For example, a particular treatment system may utilize both adsorption processes and incorporate some features of advanced oxidation treatment processes. This review aims to synthesize current literature and recent advancements to inform future research on SY removal, hence supporting sustainable wastewater treatment approaches and hybrid systems.
Keywords: Sunset Yellow; Wastewater; Adsorption; Advanced oxidation processes; Biological treatments